Integrated scheduling problem of multi-load AGVs and parallel machines considering the recovery process - Fan, Xin; Sang, Hongyan; Tian, Mengxi; Yu, Yang; Chen, Song (Swarm and evolutionary computation, 2025)
In modern manufacturing workshops, parallel machine scheduling and automated guided vehicle (AGV) scheduling are two closely coupled problems. However, the two problems are often solved independently, which reduces the performance of manufacturing system to a large extent. To address this issue, this paper investigates the integrated scheduling problem of multi-load AGV and parallel machine considering the recovery process (MAGVPM-R). Firstly, a mathematical model is established to optimize the completion time. Second, a weight priority integration heuristic (WPIH) and four neighborhood operators are designed based on MAGVPM-R characteristics. Third, a discrete grey wolf optimization (DGWO) algorithm is proposed. Finally, the mathematical model is validated using the GUROBI solver and the performance of DGWO is tested with 100 instances of different scales. The experimental results show that DGWO solves the MAGVPM-R problem better than other competing algorithms.